Pulmonary Hypertension - Hill, Nicholas S.; Farber, Harrison W. (Contemporary Cardiology,, 2008)
This timely volume addresses the areas of pathophysiology and therapy of pulmonary hypertension, which have seen exciting developments over the past decade. The discoveries of endothelin overexpression as well as prostacyclin and nitric oxide deficiency in association with pulmonary hypertension have led to important therapeutic insights. In addition, the identification of genes associated with pulmonary hypertension has just begun to open the door to new pathophysiologic insights. The new therapies have led to significant improvements in patient function, quality of life and survival. This book will be of interest not only to cardiologists, pulmonary specialists and rheumatologists, but also many nurses and pharmacotherapists are becoming increasingly involved in the therapy of patients with pulmonary hypertension.